(untitled) (Journal of Fiber Bioengineering and Informatics, 2025)
Fabric hand properties significantly influence consumer satisfaction and product quality in the textile industry. This study investigates the application of the Fabric Touch Tester (FTT) and Fabric Big Data (FBD) platform for digitising and tracing fabric hand properties during wool textile manufacturing. The research builds on prior studies, confirming that FTT effectively quantifies hand properties during manufacturing, while the FBD platform enables real-time visualisation and networked access to production data. Results reveal that this approach allows fabric properties during manufacturing to be well monitored and enable manufacturers to consider whether redundant steps could be eliminated to enhance resource efficiency. Additionally, this study demonstrates how integrating digital tools into production workflows aligns with ESG and ESPR goals by reducing waste and optimising resource use. These findings offer practical guidance for advancing sustainable textile manufacturing, laying the foundation for more intelligent and transparent production systems.